2010
DOI: 10.1007/s11064-010-0253-9
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Deficit and Decreased GABA Receptor Functional Regulation in the Hippocampus of Epileptic Rats: Effect of Bacopa monnieri

Abstract: In the present study, alterations of the General GABA and GABA(A) receptors in the hippocampus of pilocarpine-induced temporal lobe epileptic rats and the therapeutic application of Bacopa monnieri and its active component Bacoside-A were investigated. Bacopa monnieri (Linn.) is a herbaceous plant belonging to the family Scrophulariaceae. Hippocampus is the major region of the brain belonging to the limbic system and plays an important role in epileptogenesis, memory and learning. Scatchard analysis of [³H]GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…Although, the mechanism through which Bacopa monnieri ameliorates allodynia and hyperalgesia is still unknown; nonetheless, in view of its myriad pharmacological profile it can be speculated that multiple mechanisms might be involved as Bacopa monnieri possesses anti-nociceptive activity [30] mediated through opioidergic mechanisms [88], enhances the morphine anti-nociceptive effects [66], increases synaptic plasticity [97], up-regulates vesicular glutamate transporter type 2 (VGLUT2) [98] and decreases the immunodensity of glutamate/ N -methyl-D- aspartate receptor subtype 1 (NMDAR1) [99]. What is more, Bacopa monnieri increases GABA, GABA A receptor subunit, GABA A receptor binding and up-regulation of GAD gene [11]. Additionally, Bacopa monnieri decreases the release of TNF-α and IL-6 [22] and inhibits the activities of COX-2, LOX-5 and LOX-15 [21].…”
Section: Discussionmentioning
confidence: 99%
“…Although, the mechanism through which Bacopa monnieri ameliorates allodynia and hyperalgesia is still unknown; nonetheless, in view of its myriad pharmacological profile it can be speculated that multiple mechanisms might be involved as Bacopa monnieri possesses anti-nociceptive activity [30] mediated through opioidergic mechanisms [88], enhances the morphine anti-nociceptive effects [66], increases synaptic plasticity [97], up-regulates vesicular glutamate transporter type 2 (VGLUT2) [98] and decreases the immunodensity of glutamate/ N -methyl-D- aspartate receptor subtype 1 (NMDAR1) [99]. What is more, Bacopa monnieri increases GABA, GABA A receptor subunit, GABA A receptor binding and up-regulation of GAD gene [11]. Additionally, Bacopa monnieri decreases the release of TNF-α and IL-6 [22] and inhibits the activities of COX-2, LOX-5 and LOX-15 [21].…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study has found that bacopa provides protection from phenytoin-induced cognitive impairments [8]. It has been postulated that its anti-epileptic effect could be mediated through glutamate, NMDA R1 [9] and GABA receptor [10], yet another study suggested that BESEB CDRI-08 reduced hypobaric hypoxia induced spatial memory impairment [11]. Furthermore, the efficacy of a bacopa extract in learning and memory have been further established by showing the reversal of diazepam [12] and scopolamine-induced amnesia [13,14] and neuroprotective effect against cholinergic degeneration [5].…”
Section: Introductionmentioning
confidence: 98%
“…This, in turn, reduces the threshold of seizure generation and thus contributes to the onset of seizures. Furthermore, the PISE model used in this study also exhibited inverse function of GABA signaling [32]. There is evidence that seizures beget seizures and that GABA signaling plays a central role in this phenomenon [2].…”
Section: Discussionmentioning
confidence: 99%